2022
DOI: 10.5213/inj.2244052.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Automatic Interpretation Algorithm for Uroflowmetry Results: Application of Artificial Intelligence

Abstract: Purpose: To develop an automatic interpretation system for uroflowmetry (UFM) results using machine learning (ML), a form of artificial intelligence (AI).Methods: A prospectively collected 1,574 UFM results (1,031 males, 543 females) with voided volume>150 mL was labelled as normal, borderline, or abnormal by 3 urologists. If the 3 experts disagreed, the majority decision was accepted. Abnormality was defined as a condition in which a urologist judges from the UFM results that further evaluation is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Therefore, it is recommended to use repeated measurements instead of relying on a single test result to increase the reliability of the test. 4,23,24 Our study found that the patients' second UF results improved compared to the first. That may be because the patients feel more comfortable as they become familiar with the environment, recognize the health professionals, and learn how to perform the test.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Therefore, it is recommended to use repeated measurements instead of relying on a single test result to increase the reliability of the test. 4,23,24 Our study found that the patients' second UF results improved compared to the first. That may be because the patients feel more comfortable as they become familiar with the environment, recognize the health professionals, and learn how to perform the test.…”
Section: Discussionmentioning
confidence: 53%
“…That may stimulate the sympathetic nervous system, decreasing bladder capacity and potentially affecting the UF results. 4,5,9,10 Patient comfort is crucial for appropriate bladder emptying. 18 While multiple factors may affect the voiding, there is limited research on the impact of patients' emotional conditions on UF parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In predicting benign urological conditions, CT images were used to detect urinary stones [ 5 ]. Other than image analysis, AI algorithms are expanding their range including estimations of stone-free status and uroflowmetry results [ 6 7 ]. Robot-assisted surgery is most likely to be leveraged by AI.…”
Section: Ai In Urologymentioning
confidence: 99%